Quasi‐Experimental Single‐Subject Design: Comparing Seeking Safety and Canine‐Assisted Therapy Interventions Among Mentally Ill Female Inmates. Issue 1 (6th April 2020) - Holman, Leigh F.; Ellmo, Frances; Wilkerson, Shelly; Johnson, Re'Sean
Abstract : This repeated measures quasi‐experimental study evaluated the effectiveness of 2 interventions, Seeking Safety and canine‐assisted therapy, with female prisoners with trauma histories on a mental health unit. Results indicate both are effective at reducing anxiety, depression, and posttraumatic stress disorder.